Contemporary Validation of a Nomogram Predicting Colon Cancer Recurrence, Revealing All-Stage Improved Outcomes. Issue 2 (25th April 2019) - Konishi, Tsuyoshi; Shimada, Yoshifumi; Hsu, Meier; Wei, Iris H; Pappou, Emmanouil; Smith, J Joshua; Nash, Garrett M; Guillem, José G; Paty, Philip B; Garcia-Aguilar, Julio; Cercek, Andrea; Yaeger, Rona; et al.
Abstract: Background: The Memorial Sloan Kettering Cancer Center (MSK) colon cancer recurrence nomogram is a risk calculator that provides patients and clinicians with individualized prediction of recurrence following curative resection of colon cancer. Although validated on multiple separate cohorts, the nomogram requires periodic updating as patient care changes over time. The aim of this study was to evaluate the nomogram's accuracy in a contemporary cohort and modify the tool to reflect improvements in outcome related to advances in colon cancer therapy. Methods: A contemporary patient cohort was compiled, including consecutive colon cancer patients undergoing curative resection for stage I–III colon adenocarcinoma at MSK from 2007 to 2014. The nomogram's predictive accuracy was assessed by concordance index and calibration plots of predicted vs actual freedom from recurrence at 5 years after surgery. Results: Data from a total of 999 eligible patients with complete records were used for validation. Median follow-up among survivors was 37 months. The concordance index was 0.756 (95% confidence interval = 0.707 to 0.805), indicating continued discriminating power, but the calibration plot revealed that the nomogram overestimated recurrence risk. Recalibration of the nomogram by estimating a new baseline freedom-from-recurrence function restored the nomogram's accuracy. Conclusion: The updated nomogram retains the original nomogram's variables but includes a lower baseline estimation of recurrence risk, reflecting improvements in outcomes for all stages of colon cancer, likely resulting from advances in imaging and integration of multiple treatment modalities.